Analyses of permeability and porosity of sedimentary rocks in terms of unconventional geothermal resource explorations in Poland - Sowiżdżał, Anna; Semyrka, Roman (Geologos, 2016)
Petrophysical investigations are fundamental to natural resource exploration. In order to recognise the geothermal potential of sedimentary rocks in central Poland, 259 samples were collected from prospective deep-lying geothermal reservoirs. Parameters measured include bulk density, skeletal density, effective porosity, permeability, average pore diameter and specific surface. Results indicate that at great depths (mostly > 3,000 m below surface) sedimentary rocks show low values of porosity (mainly less than 5%) and permeability (only sporadically in excess of 1 md). These values call for a petrothermal use of reservoirs, for which an Enhanced Geothermal System (EGS) was developed. Reservoirs suited for the EGS are Carboniferous and Lower Triassic sandstones in the central part of Poland (Mogilno-Łódź Trough region and a small part of the Kujawy Swell and Fore-Sudetic regions). In addition, Carboniferous limestones in this area are potentially prospective.